Methods of Development the Culture of Reading in Continuous Education - Ganieva, Barno (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article includes information about research methods of development the culture of reading in continuous education which is caring out at the Tashkent University of Information Technologies. Also the forms and importance of information presentation and perception in the age of information technologies and recommendations to improve the effectiveness of the educational process in this aspect are given too.